2022
DOI: 10.3390/diagnostics12071603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Respiratory Particle Emission during Otorhinolaryngological Procedures in the Context of the SARS-CoV-2 Pandemic

Abstract: Understanding the risk of infection by routine medical examination is important for the protection of the medical personnel. In this study we investigated respiratory particles emitted by patients during routine otolaryngologic procedures and assessed the risks for the performing physician. We developed two experimental setups to measure aerosol and droplet emission during rigid/flexible laryngoscopy, rhinoscopy, pharyngoscopy, otoscopy, sonography and patient interview for subjects with and without masks. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Transmission concerns were heightened within otolaryngology, especially within the rhinology subspecialty. 1,2 A survey of rhinologists during the pandemic suggested that significant impacts to rhinologic practice were ongoing; however, impacts to clinical care have not been directly assessed longitudinally. 3 The goal of this study was to quantitatively analyze the real-world impact of the COVID-19 pandemic on tertiary rhinology practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission concerns were heightened within otolaryngology, especially within the rhinology subspecialty. 1,2 A survey of rhinologists during the pandemic suggested that significant impacts to rhinologic practice were ongoing; however, impacts to clinical care have not been directly assessed longitudinally. 3 The goal of this study was to quantitatively analyze the real-world impact of the COVID-19 pandemic on tertiary rhinology practice.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID‐19) infamously lead to a global pandemic, where social distancing orders were needed to control its spread. Transmission concerns were heightened within otolaryngology, especially within the rhinology subspecialty 1,2 . A survey of rhinologists during the pandemic suggested that significant impacts to rhinologic practice were ongoing; however, impacts to clinical care have not been directly assessed longitudinally 3 .…”
Section: Introductionmentioning
confidence: 99%